Identification of multifunctional ATP-citrate lyase kinase as the alpha-isoform of glycogen synthase kinase-3. - Hughes, K (1992)
Multifunctional ATP-citrate lyase kinase (ACLK) exhibits several properties that are similar to glycogen-synthase kinase-3 (GSK-3). The molecular cloning of two distinct mammalian GSK-3 cDNAs and a Drosophila melanogaster (fruitfly) homologue, zeste-white3sgg, has established the existence of a GSK-3 subfamily. A multifunctional protein kinase first identified as an ACLK has recently been shown to exhibit several similarities to the alpha- and beta-forms of GSK-3. Here we have used immunological and biochemical analyses to directly compare these enzymes. Thus purified preparations of ACLK isolated from brain and liver preferentially cross-react with anti-GSK-3 alpha antisera and phosphorylate previously defined substrates of GSK-3 at identical sites. Conversely, both alpha- and beta-forms of GSK-3 phosphorylated ATP-citrate lyase at the same site(s) targeted by ACLK. These, and other similarities, demonstrate ACLK to be identical with, or highly related to, GSK-3 alpha, the implications of which are discussed.